Fiscal Policies and Institutions for Shared Growth in Kenya : Lessons from the Global Crisis - World Bank (Washington, DC, 2013)
This report brings together three budget notes that assess Kenya's fiscal capacity to respond to global crisis and deliver shared growth without compromising macroeconomic stability. The report is organized into three notes. The key messages from this analysis point to areas where Kenya's fiscal policy requires strengthening. The first note is an assessment of Kenya's fiscal stance and suggests an appropriate fiscal anchor for Kenya. The second note reviews the status of public investment in Kenya and suggests the reforms required to improve public investment planning and implementation. The subject of the third note is pro-poor spending and targeted subsidy programs. This study concludes that the targeted cash transfers, unemployment benefits, and workfare programs provide automatic stabilizers for fiscal policy during crisis.